The Effect of Financial Literacy, Cost of Education and Future Orientation on Financial Well-Being in Taking Education Insurance Policie - Nurbaiti; Tuti Anggraini; Annisa Zahrina Dharmawan (Al-Kharaj: Journal of Islamic Economic and Business, 2025)
This study aims to analyze the influence of financial literacy, education costs, and future orientation on financial well-being in taking education insurance policies in Deli Serdang Regency. The background of this study is based on the low level of insurance literacy and inclusion in Indonesia, especially in education insurance products, which has implications for less than optimal family financial planning for children's education needs. Through a quantitative approach, this study examines the relationship between the three independent variables on people's financial well-being in the context of decisions to take education insurance policies. The results of the study indicate that financial literacy and future orientation have a significant positive effect on financial well-being, while the high cost of education is an inhibiting factor in making education insurance decisions. These findings emphasize the importance of financial education and increasing public awareness of future planning in order to achieve family financial well-being, as well as the need for strategies to reduce education costs so that education insurance is more affordable and inclusive.